Detecting a Possible Correlation between Hands-On Experimentation and Scientific Data Analysis in 8th Grade Students - Breana Dobesh; Phu Vu (Middle Grades Review, 2023)
This Practitioner Perspective reports on action research that examined the impact of integrating hands-on experimentation on eighth- grade students skills of scientific data analysis and interpretation in a science middle school class. The intervention given to the treatment group was tasking students with completing scientific experiments during their daily lessons, along with collecting and analyzing data from those experiments. Collected data through both control and treatment groups indicated that there was no significant difference in mean test scores between the two groups. Discussions and suggestions for future studies were included.
Keywords: middle school; hands-on experiment; data analysis